2014
DOI: 10.1371/journal.pone.0108938
|View full text |Cite|
|
Sign up to set email alerts
|

Glaucoma, Alzheimer's Disease, and Parkinson's Disease: An 8-Year Population-Based Follow-Up Study

Abstract: BackgroundGlaucoma is the leading cause of irreversible blindness worldwide and primary open-angle glaucoma (POAG) is the most common type of glaucoma. An association between POAG and the subsequent risk of Alzheimer's disease (AD) and Parkinson's disease (PD) was unclear.ObjectiveTo investigate the association between POAG (including normal-tension glaucoma) and the subsequent risk of AD or PD 8 years following a diagnosis of POAG.MethodsWe performed a retrospective, propensity-score-matched analysis of a pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 41 publications
4
85
1
3
Order By: Relevance
“…In addition, the prevalence of glaucoma is increased in AD patients; 25.9 %, compared to 1%-5.2% in the normal population [38][39][40]. The reverse correlation is less distinct as some population studies of glaucoma patients show a higher risk of AD [41], whereas others reported no association [42,43]. Possibly, AD is a risk factor for glaucoma, or AD and glaucoma share a pathophysiological process with retinal neurodegeneration as final common pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prevalence of glaucoma is increased in AD patients; 25.9 %, compared to 1%-5.2% in the normal population [38][39][40]. The reverse correlation is less distinct as some population studies of glaucoma patients show a higher risk of AD [41], whereas others reported no association [42,43]. Possibly, AD is a risk factor for glaucoma, or AD and glaucoma share a pathophysiological process with retinal neurodegeneration as final common pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Age-dependent accumulation of Aβ in RGCs has been suggested to contribute to glaucoma pathology, and anti-Aβ therapies have been identified as a therapeutic target to prevent RGC degeneration [68]. These data, coupled with reports of an increased incidence of AD among glaucoma patients [113], have led to the suggestion that glaucoma could be described as a type of ocular AD [123]. …”
Section: Mechanisms Of Rgc and Axonal Deathmentioning
confidence: 99%
“…Alzheimer-type dementia (ATD) is known as the most widespread form of dementia and is an important health problem in every country (9) . It is a progressive neurodegenerative disorder characterized by cognitive deterioration and deterioration in memory, changes in personality, behavioral disturbances, and impaired ability to perform the activities of daily life (10) . Glaucoma and dementia (especially ATD) share several features.…”
Section: Introductionmentioning
confidence: 99%